Piezoelectric surgery and navigation: a safe approach for complex cases of Eagle syndrome. Issue 10 (October 2016) - Spalthoff, S.; Zimmerer, R.; Dittmann, O.; Tavassol, F.; Dittmann, J.; Gellrich, N.-C.; Jehn, P.
Abstract: Eagle syndrome was first described by Eagle in 1937. It is associated with an elongated styloid process and/or calcification of the stylohyoid ligament, mainly resulting in pain in the orofacial region. The treatment of Eagle syndrome includes conservative treatment with physical therapy supported by medication, or surgical removal of the styloid process. Two different surgical approaches are described in the literature: the transoral and transcervical approaches. Both have their limitations and specific intraoperative risks. A modification of the transcervical approach that adds an extra security measure to the treatment of complex cases of Eagle syndrome is presented herein. The styloid process was removed by combining piezoelectric surgery, preoperative digital planning, and surgical navigation. No complication was noted, and the patient recovered quickly after surgery. A follow-up visit 2 months later showed no remaining symptoms of Eagle syndrome on the treated side. Therefore, digital planning and surgical navigation could add valuable safety measures to the treatment of complex cases of Eagle syndrome.